The roles of child maltreatment types and peer relationships on behavior problems in early adolescence. (February 2021) - Yoon, Dalhee; Yoon, Susan; Pei, Fei; Ploss, Alexa
Abstract: Background: Although previous research has established that child maltreatment (CM) and peer relationships (i.e., deviant peer affiliation, being ignored by peers) are strong predictors of adolescent internalizing (INT) and externalizing (EXT) behavior problems, no study has examined the above effects concurrently. Nor have researchers investigated the potential peer relationship differences in the effects of CM types on adolescent behavior problems. Thus, this study aims to examine the independent and combined effects of different types of CM and peer relationships on behavior problems. Methods: The Generalized Estimating Equations approach was conducted using the Longitudinal Studies of Child Abuse and Neglect. Child-Protective-Services reports and youth self-reports were used for each type of CM. Deviant peer affiliation (DP) has been assessed using a modified version of the Youth-Risk-Behavior-and-Monitoring-the-Future Survey, while being ignored by peers was assessed using a single question. Adolescent INT and EXT were measured using the Youth-Self-Report. Results: Emotional abuse was associated with both INT and EXT, whereas physical abuse was associated with EXT. Higher DP and higher incidence of being ignored by peers were both associated with higher levels of INT and EXT. Emotionally abused youth with higher levels of DP had less INT, compared to emotionally abused youth with lower levels of DP. Conclusion: The Findings indicate the need for interventions that 1) take into account the different effects of CM types, specifically for emotionally abused youth; 2) help youth to build positive relationships with peers; and 3) work to reduce the possibility of affiliation with deviant peers.